Plasma Exosomal Long Non-Coding RNAs Serve as Biomarkers for Early Detection of Colorectal Cancer - Hu, Dongzhi; Zhan, Yang; Zhu, Kegan; Bai, Ming; Han, Jiayi; Si, Yiran; Zhang, Haiyang; Kong, Dalu (Cellular physiology and biochemistry, 2019)
Background/Aims: Colorectal cancer (CRC) is the third most commonly diagnosed malignancy and the second leading cause of cancer-related deaths worldwide. Thus, methods for early diagnosis of CRC are urgently needed. We aimed to identify potential long non-coding RNAs (lncRNAs) in circulatory exosomes that may serve as biomarkers for the detection of early-stage CRC. Methods: Exosomes from the plasma of CRC patients (n = 50) and healthy individuals (n = 50) were isolated by ultracentrifugation, followed by extraction of total exosomal RNAs using TRIzol reagent. Microarray analysis was used for exosomal lncRNA profiling in the two groups, and real-time quantitative reverse transcription-polymerase chain reaction (qRT-PCR) was used to determine the expression level of lncRNAs in all patients and healthy subjects. Results: The expression of six lncRNAs (LNCV6_116109, LNCV6_98390, LNCV6_38772, LNCV_108266, LNCV6_84003, and LNCV6_98602) was found to be significantly up-regulated in CRC patients compared with that in healthy individuals by qRT-PCR. The receiver operating characteristic curve was used to verify their diagnostic accuracy. The values of the area under the curve for these lncRNAs were 0.770 (LNCV6_116109), 0.7500 (LNCV6_98390), 0.6500 (LNCV6_38772), 0.6900 (LNCV_108266), 0.7500 (LNCV6_84003), and 0.7200 (LNCV6_98602). Conclusion: Our study suggested that the expression of these six exosomal lncRNAs (LNCV6_116109, LNCV6_98390, LNCV6_38772, LNCV_108266, LNCV6_84003, and LNCV6_98602) was significantly up-regulated in the plasma of CRC patients, and that they may serve as potential non-invasive biomarkers for early diagnosis of CRC.